2017
DOI: 10.1016/j.jshs.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

How does high-intensity intermittent training affect recreational endurance runners? Acute and chronic adaptations: A systematic review

Abstract: ObjectiveThis systematic review aimed to critically analyze the literature to determine how high-intensity intermittent training (HIIT) affects recreational endurance runners in the short- and long-term.MethodsElectronic databases were searched for literature dating from January 2000 to October 2015. The search was conducted using the key words “high-intensity intermittent training” or “high-intensity interval exercise” or “interval running” or “sprint interval training” and “endurance runners” or “long distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 66 publications
1
21
0
1
Order By: Relevance
“…is instrument is used for quality assessment of observational studies and randomized clinical studies and comprises 27 items totalling up to 32 points (higher scores indicating superior quality). In this review, a modified version [22][23][24][25][26][27][28] of this instrument was used which consisted of 17 items (1-3, 5-7, 9-11, 16-18, 20-22, and 25-26), totalling up to a maximum of 17 points. e relevant domains for the instrument included description, external validity, and internal validity (confusion/ selection bias).…”
Section: Bias Risk Assessmentmentioning
confidence: 99%
“…is instrument is used for quality assessment of observational studies and randomized clinical studies and comprises 27 items totalling up to 32 points (higher scores indicating superior quality). In this review, a modified version [22][23][24][25][26][27][28] of this instrument was used which consisted of 17 items (1-3, 5-7, 9-11, 16-18, 20-22, and 25-26), totalling up to a maximum of 17 points. e relevant domains for the instrument included description, external validity, and internal validity (confusion/ selection bias).…”
Section: Bias Risk Assessmentmentioning
confidence: 99%
“…Bradbury et al found that linear and reverse linear periodization generated greater improvements in endurance performance, RE, and VO 2 max in recreational runners than nonperiodized progression of training load [44]. Further, when considering previous studies including the use of HIIT and SIT in recreational runners, it may be suggested that, during the training period, recreational runners should adopt a linear periodization when using HIIT (from high to low volume and from low to high intensity) and a reverse linear periodization when using SIT in order to increase performance [10,14,16,18,45], following the principle of progressive overload. In addition, a general recommendation from our practical experience would be that either block or linear periodization may fit better with short or moderate distances (21 km or shorter), while performance in marathons and longer events would probably benefit from reverse periodization.…”
Section: Training Periodizationmentioning
confidence: 99%
“…Countless recreational runners train hard to improve their distance performance (Garcá ƒa-Pinillos et al, 2017). At present, many laboratories and sports facilities have expired gas analyzers, and the treadmill running test may be more accessible to recreational runners.…”
Section: Introductionmentioning
confidence: 99%